2019
DOI: 10.1002/adem.201801232
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Hot Workability for a Near Alpha Titanium Alloy by Integrating Processing Maps and Constitutive Relationship

Abstract: Hot workability of near‐alpha titanium alloy Ti–6Al–3Nb–2Zr–1Mo with an initial duplex microstructure is evaluated through isothermal compressions in lower α + β phase field, upper α + β phase field, and β phase field. It is noteworthy that flow stress increases with increasing strain rates and decreasing temperatures. Based on Dynamic Material Model and Prasad's instability criterion, processing maps are established and subdivided into six characterization regions to ascertain deformation mechanisms connected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…In this model, the workpiece is regarded as a power dissipater. The total power P in the process of system deformation can be considered as two harmonizing parts [ 39 , 40 ]: where G represents the power dissipation due to plastic deformation, and J the power dissipation associated with the change of microstructure. The fraction of power which is absorbed by deforming the material during hot processing is called the efficiency of power dissipation, η .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this model, the workpiece is regarded as a power dissipater. The total power P in the process of system deformation can be considered as two harmonizing parts [ 39 , 40 ]: where G represents the power dissipation due to plastic deformation, and J the power dissipation associated with the change of microstructure. The fraction of power which is absorbed by deforming the material during hot processing is called the efficiency of power dissipation, η .…”
Section: Resultsmentioning
confidence: 99%
“…In this model, the workpiece is regarded as a power dissipater. The total power P in the process of system deformation can be considered as two harmonizing parts [39,40]:…”
Section: Processing Mapmentioning
confidence: 99%
“…The above-mentioned research work on duplex phase titanium alloys are worth mentioning for recognizing the flow stress behavior, microstructure, and texture evolution of the material during hot deformation [10][11][12][13]. The relevant studies can provide reference for the current work.…”
Section: Introductionmentioning
confidence: 98%
“…The results demonstrated that the processing parameters have a significant effect on the softening mechanism. Zhou et al [11] researched the characterization of hot workability for Ti80 alloy by integrating processing maps and establishing a constitutive relationship. Xu et al [12] studied the flow softening and microstructure evolution of Ti-17 alloy and found that the microstructure evolution of alpha and beta phases together influence flow softening.…”
Section: Introductionmentioning
confidence: 99%
“…By now, considerable investigations have intensively focused on the descriptions of hot deformation behaviors for diverse metals. Phenomenological constitutive models, such as Field–Backofen (F–B) model, [ 4 ] Johnson–Cook (JC) model, [ 5–7 ] Arrhenius hyperbolic‐sine equations, [ 8–12 ] and Cingara–Queen (C–Q) equations, [ 13,14 ] are developed to precisely characterize the flow characteristics of hot deformed alloys. [ 15,16 ] Considering the specific deformation mechanisms such as dislocation motion, work hardening (WH), dynamic recrystallization (DRX), and dynamic recovery (DRV), a series of physically based constitutive models, including Voyiadjis–Abed (VA) model, [ 17–19 ] Zerilli–Armstrong (Z–A) model, [ 20–22 ] unified dislocation density‐based model, [ 23–27 ] and two‐stage physically based constitutive equations, [ 28–33 ] are used to model the flow behaviors of alloys.…”
Section: Introductionmentioning
confidence: 99%